Audit program adressed to human resource assessment system of health and safety in food marketing companies (case MERCABAR) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This paper is intended to propose a human resource audit program for hygiene and safety system work in food marketing companies, taking as a case study the Wholesale Food Market in Barquisimeto, MERCABAR CA. This work was framed in the context of descriptive study design field in non-experimental trans. Direct observation, semi-structured interviews, and questionnaires administered to a selected sample of all employees working in the company were used. To carry out the analysis results, statistical means and an analysis matrix were used that allowed interpretation of data obtained. This study is highly relevant, because it conceived information about the current situation of occupational health and safety of one of the food market centers in the country such as MERCABAR CA, which will serve to correct and improve possible failures an organization in this area could have. It also contributes to take actions and guidelines for the company to avoid risk of incidents at work, accidents at work and occupational diseases workforce might go through, and possible sanctions for breaching parameters established in the current legislation in this area. The data allowed an audit program proposal, which will serve as a tool for public accounting professional to assess the occupational health and safety in this type of organization which are important for the nation food supply.
Keywords: human resource audit; hygiene and occupational safety; risk; workers